Risky Sexual Behavior Profiles in Youth: Associations With Borderline Personality Features - Bégin, Michaël; Ensink, Karin; Bellavance, Katherine; Clarkin, John F.; Normandin, Lina (Frontiers in Psychology, 2022)
Adolescence and young adulthood are peak periods for risky sexual behaviors (RSB) and borderline personality disorder (BPD) features. RSB is a major public health concern and adolescents with BPD may be particularly vulnerable to RSB, but this is understudied. The aim of this study was to identify distinct RSB profiles in youth and determine whether a specific profile was associated with BPD features. Participants were 220 adolescents and young adults (age 14–21) recruited from the community. To identify groups of adolescents and young adults who engage in similar RSB, a latent profile analysis (LPA) was conducted on sexually active youth (57%). Next ANOVA was used to identify how profiles differed in terms RSB dimensions and BPD features. We identified three distinct RSB profiles: (1) a Low RSB profile that was manifested by the majority (77.7%) of youth; (2) an Unprotected Sex in Relationships profile (13.3%) and; (3) an Impulsive Sex Outside Relationships profile (12%) which was manifested by youth with significantly higher BPD features. The findings shed light on the difficulties youth with BPD manifest around integrating sexuality, intimacy, fidelity, and love. This contrasts with the majority of youth who are sexually active in the context of relationships and engage in little or no RSB. The findings have important clinical implications. Adolescent sexuality is frequently in the blind spot of clinicians. To address the elevated risk of RSB in adolescents with BPD, interventions are needed to help adolescents navigate this period and improve their understanding of the reasons for RSB while addressing difficulties in establishing sexual and attachment relationships.